Medical education during the Covid-19 pandemic long-term experiences of German clinical medical students - Marc Gottschalk; Pascal M. Milch; Christian Albert; Katrin Werwick; Ruediger C. Braun-Dullaeus; Philipp Stieger (PLoS ONE, 2023)
Introduction Due to the Covid-19 pandemic and the accompanying hygiene regulations, medical students in Germany faced multiple educational and personal challenges. The challenges included the cancellation and digitalisation of courses, the closing of university institutions such as libraries, a decrease in social contacts, and the risk of a Covid-19 infection. The aim of this study was to understand medical students’ pandemic experiences as well as the consequences of these experiences for the students’ future work as physicians. Materials and methods We performed 15 guided, one-on-one interviews with clinical medical students (third to fifth year) at the Otto-von-Guericke-University Magdeburg. Interviews were recorded, transcribed, and anonymised. We performed a qualitative content analysis in accordance with Mayring and thereby formed an inductive category system. The Consolidated Criteria for Reporting Qualitative Research (COREQ) were applied. Results Five categories were inductively formed: “Changes in the teaching experience”, “negative effects on the learning experience”, “decrease in personal social contacts”, “contact with covid-19”, and “pandemic-associated stress increase”. The participating students reported higher levels of stress due to isolation and uncertainty regarding their educational future. Furthermore, students welcomed the digitalisation of lectures, developed individual coping strategies, and voluntarily took part in the care of Covid-19 patients. Limitations to social interactions were perceived as the major restrictive factor to their educational structure, their perceived learning success and personal development. Conclusion This study identified social restrictions as well as didactic and academic structural challenges as relevant factors contributing to perceived stress and fear for medical students during the Covid-19 pandemic, especially as regards their learning experience. Students’ acceptance of digitalised learning may enable regular interaction with university peers and may facilitate a structured educational life. However, the implementation of digital resources could not provide a sufficient substitute for in-person courses.